The Influence Of Ratio Chocolate With Dadih To The Quality Of Sensory Praline Dadih - Aimuni, Nurul; Faridah, Anni (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Lack of public knowledge of west Sumatra's typical functional food, namely "dadiah". Dadiah is a buffalo milk product that is fermented naturally in bamboo containers at room temperature for 24 - 48 hours. Dadiah has a sour taste and fishy aroma that is not liked by some people or the public, the use of chocolate can reduce the sour taste and fishy aroma in dadiah, one of which is by being made into praline dadiah.  This study aims to analyze the ratio of chocolate to dadiah to the quality of praline dadiah as much as (4:5); (5:5) and (6:5) to the qualities of shape, color, aroma, texture, taste and liking. This type of research is a pure experiment that uses a complete randomized design method and three repetitions carried out by giving questionnaires to limited panelists. The instruments used are organoleptic tests through level tests, hedonic tests, and hypothesis testing using ANOVA statistics, and if they differ significantly followed by the Duncan Test.  The results showed that the average values were almost the same in every test except for the quality of texture and likeability. This is also evidenced by the results of ANOVA, where the texture and preferences of the praline are influenced by the large ratio of chocolate. The best results are found in the ratio (5:5) in each praline dadiah manufacturing treatment